Pelatihan Penghitungan PPh Final Tarif 0.5% Sesuai Peraturan Pemerintah No.55 Tahun 2022 pada Pelaku Usaha UMKM di Kepulauan Banda Neira, Kabupaten Maluku Tengah - Husein, Hartina; Basuki, Ferry H; Pattinaja, Elna Marsye; Temalagi, Selva; Kriswantini, Dwi; Lewaru, Trisna Sary (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The untapped potential for taxation in Indonesia is still quite high, one of which is "underground economy" activities which have not been identified because the original transactions are using cash. Apart from that, taxpayers' knowledge is still subsided, which results in a combination of high levels of tax avoidance and evasion. Provides knowledge related to tax reporting, as well as financial reporting understandability to some of entrepreneurs is an urgent activity to deal with, is the responsible of academics to lowering this gap. Based on a pre-survey of 23 entrepreneurs, it was found that none of them had a NPWP (Taxpayer Identification Number) and had never had association with tax agencies. This PKM is held in intermediary with the learning of tax ability for entrepreneurs who have certain Gross Income with a maximum limit of 4.8 billion per year. By providing facilities from the government through a classification of 0.5% rate of the DPP. It is an opportunity for entrepreneurs to submit taxes. The results of the PKM result that most of the material has been enlightened, but the issue of this PKM can be seen from the compliance of entrepreneurs with tax obligations, which is expected in a more acceptable way in the future.